LABOUR PRODUCTIVITY OF BLOCKWORK ACTIVITY IN SELECTED PUBLIC BUILDING PROJECTS IN AKWA IBOM STATE, NIGERIA (Malaysian Journal of Civil Engineering, 2018)
This study aims at establishing labour productivity norm and assignable causes of variability of construction labour productivity for blockwork activity. A descriptive survey research design approach was adopted. Data were collected on a gang comprising of a bricklayer and mate for 30 working days using project work study manual as the research instrument. Descriptive statistics and statistical control charts were the tools used for analysis. The results show that the average and baseline construction labour productivities of blockwork activity are 0.83m2/hr and 1.07m2/hr respectively. Variability in construction labour productivity of blockwork activity was observed to be due to assignable causes of weather condition and delay in supply of materials. It is recommended that ample consideration should be given to the effect of adverse weather condition during labour cost estimation by taking into cognisance the period of execution of the project. Similarly, adequate planning of construction resources will help in enhancing labour productivity on public building projects